The Role Of Islamic Banks In Yemen In Supporting Microfinance Institutions - Salem Al-Harethi, Abobakr Ramadhan (IKONOMIKA, 2018)
Islamic banks become the best solution to the crisis of the global financial system at present.in addition, it  become  also a real player in dealing with economic crises and the financial complexities of the traditional banking system prevailing in the world today. moreover, countries and governments in both developed and developing countries have become increasingly interested in the issue of microfinance because of their close association with the development in various countries and may be interested in supporting countries and governments for microfinance by enacting the necessary laws and legislation. And the establishment of institutions and bodies specialized in financing and support these microfinance in addition to the microfinance in many developed countries have become a specialty taught in universities and specialized institutes. Scientific seminars and conferences are held in order to support and develop it so that it achieves the objectives set for it and thus meets the aspirations of society in development. This study focus on the role of Islamic banks that can play an active and influential role in generating wealth and reducing poverty through financing for Microfinance institutions where the study showed the social role of the nature of contracts in Islamic banks through which Islamic banks can be the best in Microfinance. Keywords : Islamic banks, Microfinance institutions, Yemen